2019
DOI: 10.1002/jor.24559
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Suspension Allograft Modulates Inflammation in a Rat Pain Model of Osteoarthritis

Abstract: Osteoarthritis (OA) affects over 301 million adults worldwide. Inflammation is a recognized component of the OA process; two potent pro-inflammatory cytokines involved in OA are interleukin-1β and tumor necrosis factor-α. Placental-derived tissues and fluids are known to contain anti-inflammatory and immunomodulatory cytokines and growth factors. The objective of this study was to evaluate the anti-inflammatory effects of amniotic suspension allograft (ASA) in an in vivo model of OA; we evaluated pain, functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 49 publications
3
26
0
Order By: Relevance
“…The potential for extended persistence of placental tissue preparations (including PTP-001) in the joint may also help to address a challenging limitation of IA injection therapies, namely rapid clearance from the synovial space 38 . Another preclinical study measured the effects of a placental tissue product in a rat model of monoiodoacetate induced OA 39 , and reported significant reductions for both weight-bearing pain measurements and joint inflammation following treatment. In the current study, PTP-001 demonstrated substantial reductions in pain responses in a rat model of surgically induced OA, with significant effects seen as early as 1 weeks after IA dosing (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for extended persistence of placental tissue preparations (including PTP-001) in the joint may also help to address a challenging limitation of IA injection therapies, namely rapid clearance from the synovial space 38 . Another preclinical study measured the effects of a placental tissue product in a rat model of monoiodoacetate induced OA 39 , and reported significant reductions for both weight-bearing pain measurements and joint inflammation following treatment. In the current study, PTP-001 demonstrated substantial reductions in pain responses in a rat model of surgically induced OA, with significant effects seen as early as 1 weeks after IA dosing (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Saline-treated joints showed an average incidence of 2.8 ± 0.2 erosion, 2.4 ± 0.4 lesion, and an average lesion volume of 0.00725 ± 0.005 mm 3 , whereas the AM suspension showed significant reduction in erosion sites (1.2 ± 0.374) and no lesions ( 23 ). Another study using amnion suspension (total joint score, 13.7 ± 0.2) 7 d after OA induction showed no significant improvement in the joint scores compared to the control group (total joint score, 13.5 ± 0.4) ( 41 ) in an MIA-induced OA model. Another study demonstrated a dose-dependent benefit of particulate AM along with umbilical cord tissue in attenuating OA.…”
Section: Discussionmentioning
confidence: 96%
“…Intraarticular injection of amnion suspension in a monosodium iodoacetate (MIA) OA model has been previously shown to reduce joint swelling on day 14 (0.7 mm). However, an increase in the joint swelling was noticed on day 21 (1.1 mm) ( 41 ). In the present study, all three treatment groups, ADSC (0.8 ± 0.3, P < 0.001), AM gel (0.5 ± 0.1, P < 0.0001), and AM-ADSC (0.4 ± 0.1, P < 0.0001), significantly reduced joint swelling compared to the control group (1.4 ± 0.8) at day 28.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Kimmerling et al created a chemically induced OA model in rat knees and treated with saline, triamcinolone, or ASA in 25 μL or 50 μL doses. On behavioral assays, they noted significant improvements in pain threshold with decreased weight-bearing aversion and swelling in the ASA-treated rats; however, there were no differences in histological grading scores 35 In the highest-quality study to date, Farr et al conducted a multicenter randomized controlled trial of ASA injections for knee OA. They randomized 200 patients to receive ASA, hyaluronic acid (HA), or saline injections, with the subjects blinded to their treatment allocation.…”
Section: Discussionmentioning
confidence: 99%